Drug-resistant tuberculosis can be predicted by Mycobacterial interspersed repetitive unit locus - Yu-feng, Wen; Chao, Jiang; Xian-feng, Cheng (Frontiers in Microbiology, 2015)
The MIRU-VNTR (Mycobacterial Interspersed Repetitive Unit-Variable Number of Tandem Repeat) typing has been a widely-used molecular method for Mycobacterium tuberculosis genotyping. It is unknown whether MIRU-VNTR is associated with drug resistance of Mycobacterium tuberculosis. The purpose of this study was to explore the ability of twenty-four MIRU loci to predict the drug resistance of Isoniazid (INH), Rifampicin (RFP), Streptomycin (SM), Ethambutol (EMB) and Pyrazinamide (PZA). We collected the drug resistance and twenty-four MIRU loci information of 109 strains of Mycobacterium tuberculosis from an open database. The results of multivariate logistic regression showed that the variable number of tandem repeat polymorphism of MTUB04 was related to INH resistance (odds ratio (OR) = 2.82, p=0.00), RFP resistance (OR =1.91, P=0.02), SM resistance (OR=1.98, P=0.01) and EMB resistance (OR = 1.95, P=0.03). MIRU40 was associated with INH resistance (OR = 2.22, P=0.00). MTUB21 was connected with INH resistance (OR=1.63, P=0.02) and SM resistance (OR=1.69, P=0.01). MIRU26 was correlated with SM resistance (OR=1.52, P=0.04). MIRU39 was associated with EMB resistance (OR=4.07, P=0.02). The areas under receiver operating characteristic curve of INH, RFP, SM, EMB and PZA resistance prediction models were 0.84, 0.70, 0.85 and 0.74 respectively. Our results showed that MIRU loci were related to anti-tuberculosis drug and could predict the drug resistance of tuberculosis.